Performance evaluation of transmission of electricity in the sip–lines in electric distribution networks - Романовський, Володимир Ігорович; Качан, Максим Вікторович (Eastern-European Journal of Enterprise Technologies, 2014)
A method of performance evaluation of electricity transmission through modern electricity transmission SIP-lines of electric distribution networks in conditions of abruptly variable, nonlinear and asymmetric operation mode of electricity consumers was proposed in the paper. The specified operation mode of consumers meet modern operation conditions of the electrical network and is almost not considered in existing calculation methods of the actual electricity losses in the network that does not allow to adequately assess real energy efficiency of electric networks. The proposed evaluation method of electricity losses is based on measuring the current THD and values of harmonic components of currents and voltages in the network that allows to use existing measuring instruments - electricity quality analyzers for evaluation. The relationship between the measured electricity quality parameters and the instantaneous voltage change rate allows to estimate the share of electricity losses, which is caused by abruptly variable, nonlinear and asymmetric operation mode of consumers. Application of the developed method allows to assess the level of additional electricity losses in order to analyze the causes of the deterioration of electricity transmission efficiency, reduce these losses and increase energy efficiency of electricity transmission through the network. It was shown that in the modern electric distribution networks, additional electricity losses are almost 10% due to the presence of higher harmonic components of currents and voltages in the electric network.